MOCVD growth and characterization of al-rich ALN/ALGAN epilayers and quantum wells - Al Tahtamouni, Talal Mohammed Ahmad (Kansas State University, 2007)
The correlation between polarity and material quality of un-doped Al[0.81subscript]Ga[0.19subscript]N was studied. The overall material quality is significantly influenced by the growth polarity. The epilayers with aluminum-polarity have a much higher crystalline quality and better surface morphology than those of nitrogen-polarity. Nitrogen-polar growth more readily incorporates unintentional impurities. A-plane AlN epilayers have been grown on r-plane sapphire substrates. The orientation and high crystalline quality were confirmed by x-ray diffraction (XRD) [Theta]-2[Theta] scan exhibiting a reflection peak at 2[Theta] = 59.4[0superscript] and rocking curve of the (110) reflection having a line width of 940 arcsec. Room temperature photoluminescence (PL) spectroscopy showed that the surface emission intensity of a-plane AlN epilayers is comparable to that of c-plane AlN. PL spectra of Mg-doped a- and c-plane AlN revealed that the Mg level in both a- and c-plane AlN is identical and is about ~ 0.5 eV. Identically designed a-plane and c-plane AlN/A1[0.65subscript]Ga[0.35subscript]N QWs have been grown on a-and c-plane AlN/Al[2subscript]O[3subscript] templates respectively, and their PL emission properties were studied. Low temperature PL characteristics of a-plane QWs are primarily governed by the quantum size effect, whereas those of c-plane QWs are significantly affected by the polarization fields. The growth of AlN epilayers on SiC substrates was investigated. A smooth, crack free AlN epilayer with high optical and crystalline quality was achieved. Because of its high quality, AlN was used as active layer in a hybrid Schottky photodetector. Highly conductive Si-doped Al[subscript0.75]Ga[0.25subscript]N alloys were grown on AlN/SiC templates. The effects of using Indium as a surfactant during the growth of Si-doped Al[0.75subscript]Ga[0.25subscript]N epilayers at relatively high temperature 1050 [degrees]C were studied. Indium significantly increases the doping efficiency as shown by RT Hall measurements. RT PL measurements show a clear correlation between emission intensity of the defect related transition and indium flow rate. P-type conductivity has been obtained in beryllium doped GaN by MOCVD. The activation energy of the beryllium acceptor was estimated to be 118 [plus or minus] 4 meV, which is about 40 meV less than the activation energy of the Mg acceptor in GaN.
Keywords: Nitrides growth; Metal organic chemical vapor deposition; Physics, Condensed Matter (0611)